Examining meadow habitats - King, Zelda (New York : PowerKids Press, 2009)
Uses graphic organizers, simple text, and photographs to provide an introduction to meadow habitats and the plants and animals that live in them.
Includes index.
5.2
3-6
Keywords: Meadow ecology -- Juvenile literature; Meadows -- Juvenile literature; Meadow ecology; Meadows; Meadow ecology; Meadows